ANALISIS PEMBELAJARAN BERDIFERENSIASI BAGI SISWA DISGRAFIA DI SDN 013 SANGATTA UTARA - Silva Nita Ananta Putri; Nur Wulandani; Dwiyatmi Sulasminah; Faryana Maharadhika (STKIP Subang, 2026)
This research is motivated by the challenges faced by teachers in implementing the Independent Curriculum for students with specific learning disabilities in inclusive schools. The main problem observed was the presence of students with writing disabilities (dysgraphia), who required adjustments to instructional strategies in regular dasses. The purpose of this study was to analyze the implementation of differentiated learning in meeting the learning needs of students with dysgraphia at SDN 013 Sangatta Utara, as well as to identify the obstacles and efforts made by teachers. The methodology used was a descriptive qualitative approach with the primary data collection technique through in-depth interviews with class teachers selected using purposive sampling. Data analysis was conducted using the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing. The results showed that the implementation of differentiated learning had been running adaptively through the cycle of initial assessment, content differentiation, process, and product. The use of smart TV visual media and peer tutoring strategies proved effective in improving the writing skills of student N, from initially only being able to spell letters to being able to compose complete words. However, this implementation remains reactive and focused on individuals with special needs, and is hampered by teachers' lack of special education (PLB) background and the absence of written operational policies (SOPs) from schools. This study recommends strengthening internal school regulations and increasing the number of Special Guidance Teachers (GPK) to optimize inclusive practices.